Pendidikan Berbasis Cinta - Asef Umar Fakhruddin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Education with love as its basic will shape and develop children potential. A Child should able to do activity that good and rational. A teacher and parent are just spectators, who suggest correction when something unwise and dangerous happen to children and everyone else. Creativity forming on love based education is direct student to always creative. Therefore, this conception is a criteria that he applying spiritual quotient. Intelligent people spiritually will not solve live problem just rationally or emotionally. But, he will relate it will life meaning spiritually, connect it with spiritual legacy as sacred texts or saint saying to give interpretation to recent situation.